Comparison of 240 ka long organic carbon and carbonate records along a depth transect in the Timor Sea: Primary signals versus preservation changes. (21st May 2014) - Liu, Wei; Baudin, François; Moreno, Eva; Dewilde, Fabien; Caillon, Nicolas; Fang, Nianqiao; Bassinot, Franck
Abstract Total organic carbon (TOC) and calcium carbonate (CaCO3) records from different water depths in the Timor Sea (NE Indian Ocean) are compared in order to better reconstruct past changes in pelagic productivity, highlight the impact of preservation at depth, and unravel the interplay of organic carbon and carbonate sedimentation. New data are presented for core MD01‐2376 located at 2376 m depth. These results are compared, over the last 240 ka, with published data on two neighboring cores (MD01‐2378, 1783 m and MD98‐2166, 3875 m). TOC fluctuations show strong glacial/interglacial variations and Milankovitch‐type oscillations (i.e., dominant frequencies centered on the 100, 41, and 23 ka bands), with an enrichment during cold periods that reflects an increase in primary productivity as well as a lesser decomposition of organic matter with depth. During interglacials, TOC values are lower and show a stronger gradient with depth of deposition than during glacials. This suggests an overall better ventilation of deepwater masses and a steeper vertical gradient in the oxygen content, possibly associated to the upward extension of the oxygen‐rich deep waters relative to the glacial situation. Temporal fluctuations in the CaCO3 records do not show such a glacial‐interglacial pattern but reveal precession‐ and obliquity‐related oscillations. Fluctuations in the 19–23 ka bands are only observed in the shallowest core, while fluctuations in the 41 ka band are clearly expressed in the two deepest cores, suggesting that this signal is more directly related to changes in carbonate preservation at the seafloor.